Evaluation of vitamins/tonics prescribing pattern in tertiary care teaching hospital and private sector - Bhardwaj, V. K.; Budania, Navin; Kumar, Naveen; Mondal, Arka; Lata, Suman; Sharma, Monika; Kumar, Ritesh (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Rational use of drugs had been great concern by the government as well as public during the past several years. Monitoring of prescriptions studies could identify the associated problems and provide feedback to the prescribers, so as to create awareness about the irrational use of drugs. This study was conducted to evaluate the prescribing pattern of Vitamins/Tonics in government sector and private sector. Methods: This prospective study was designed to obtain statistical data on the prescribing pattern of Vitamins/tonics in patients of S.V.B.P. Hospital Meerut and other associated hospital/ clinics. The total study sample size was of 614 prescriptions. Out of these 439 prescriptions were from government sector, 175 prescriptions from private sectors. Results: Percentages of prescription with Vitamins/ Tonics were 35.76 and 48.57 in government and private sectors respectively and these differences are statistically significant. Percentage of drug prescribed as Vitamins/ Tonics of the total drugs was 8.68 and 10.19, in government and private sector respectively and these differences are statistically not significant. Vitamins/ Tonics were the most frequently prescribed drugs 16.52% and 17.14% in obs./ Gynae in both the sectors respectively, and least number of Vitamins/ Tonics 1.06% and 3.2% were prescribed in cardiology in both the sectors. Conclusions: The study indicates a big scope for enhancing the prescribing pattern of Vitamins/Tonics and minimizing the use of irrational Vitamins/Tonics, due to the fact most of the times it’s not needed, and it only put financial burden on Patients.